The monocyte-to-high-density lipoprotein ratio is associated with the occurrence of atrial fibrillation among NAFLD patients: A propensity-matched analysis - Wang, Leigang; Zhang, Yao; Yu, Bing; Zhao, Jianqi; Zhang, Wenjing; Fan, Hongxuan; Ren, Zhaoyu; Liang, Bin (Frontiers in Endocrinology, 2023)
Background: Accumulating evidence suggests that patients with nonalcoholic fatty liver disease (NAFLD) have a significantly high risk of incident atrial fibrillation (AF). Systemic inflammation, metabolic disorders and oxidative stress could be the potential mechanisms by which NAFLD drives AF. Monocyte-to- high-density lipoprotein ratio (MHR) has emerged as a novel biomarker of inflammation and oxidative stress that has not been studied in AF with NAFLD patients. We aimed to investigate the relationship between MHR and the risk of AF among NAFLD patients. Methods: A retrospective analysis was performed for the clinical data of the patients with NAFLD in the Second Hospital of Shanxi Medical University from January 2019 to October 2022, among whom 204 patients with AF were enrolled as NAFLD+AF group and 613 patients without AF were enrolled as NAFLD control, and 152 patients were selected from each group based on propensity score matching (PSM) at a ratio of 1:1 to balance the covariates between groups. Results: Univariate analysis showed that AF patients had higher MHR than non-AF patients (P < 0.001). Meanwhile, compared with pure NAFLD patients, multivariate logistic regression analysis showed that MHR remained to be an independent risk factor for AF after adjusting for confounding risk factors (OR = 10.67, 95% CI 2.17-52.37, P = 0.004). TC、HDL-C were also independent risk factors for AF. Among them, TC and HDL-C are protective factors for AF. The trend chi-square test showed that the risk of AF increased with an increase in MHR (P < 0.05). However, the RCS showed a nonlinear and J-shaped relationship between MHR and the risk of AF (P for non-linearity = 0.023). The occurrence of AF increased with increasing MHR only when MHR > 0.44. The ROC curve showed that MHR combined with traditional risk factors can improve the ability to predict AF. Conclusions: MHR is an independently associated with incident AF in patients with NAFLD and show a certain predictive value.